2018
DOI: 10.1016/j.atherosclerosis.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

A Belgian consensus strategy to identify familial hypercholesterolaemia in the coronary care unit and its subsequent cascade screening and treatment: BEL-FaHST (The BELgium Familial Hypercholesterolaemia STrategy)

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the author's institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Research to determine the clinical threshold for FH genetic testing are also underway in other regions of the United Kingdom; the Wales FH service recently developed criteria for selecting patients for FH genetic testing by modifying DLCN scoring criteria and determined a score of ≥6 to be the proper threshold to offer FH genetic testing to the Welsh population [56]. In addition, the The BELgium Familial Hypercholesterolaemia Strategy (BEL-FaHST) recently indicated that genetic testing is not recommended in cases of definite FH per DLCN criteria (if >8) [57].…”
Section: Discussionmentioning
confidence: 99%
“…Research to determine the clinical threshold for FH genetic testing are also underway in other regions of the United Kingdom; the Wales FH service recently developed criteria for selecting patients for FH genetic testing by modifying DLCN scoring criteria and determined a score of ≥6 to be the proper threshold to offer FH genetic testing to the Welsh population [56]. In addition, the The BELgium Familial Hypercholesterolaemia Strategy (BEL-FaHST) recently indicated that genetic testing is not recommended in cases of definite FH per DLCN criteria (if >8) [57].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of FH in relatives was thus based only on clinical and biological data using the DLCN criteria [1] as well as the age-specific LDL-C diagnostic cut-offs of the MEDPED FH criteria [9]. As previously published [10], the MEDPED FH criteria can be readily used in Belgium as the distribution of LDL-C levels in the general Belgian population (131 ± 34 mg/dl) [11] is almost identical to that of the general US population (130 ± 31 mg/dl). We considered various categories of likelihood of FH amongst the relatives: those with DLCN above 8 (DLCN definite FH), those with DLCN 6 and 8 (DLCN probable FH), those with positive MEDPED FH criteria (MEDPED probable FH) whereas the remaining with DLCN < 6 were considered to have no FH.…”
Section: Predesigned Diagnosis Procedures For Fhmentioning
confidence: 99%
“…Recently, Brian Starr et al [12] published age and gender-specific LDL-C diagnostic cut-offs which are based on the same principles than the classical MEDPED FH criteria but give more balanced specificity and sensitivity (significantly higher). To adjust for the difference in mean LDL-C levels between the population of the Netherlands and Belgium, we refered to different sets of published epidemiological data of LDL-C values (median) in the Belgian cohort of the the Asklepios Study [11] and in the Netherlands [10,13] (Supplementary Table 1). These "BEL-MEDPED FH cutoffs" were applied to the first relatives in a cascade screening manner: we applied it first to the first-degree relatives of the IP, and thereafter to the first-degree relatives of the "affected" first-degree relatives and so on.…”
Section: Establishment Of Rapid Rule-out Criteria For Fhmentioning
confidence: 99%
“…In Denmark only about 12 % of the individuals with FH have been identified (4). In other countries elaborate screening interventions have raised the rate of identified FH patients significantly (4,7,8).…”
Section: General Population Study Familial Hypercholesterolaemia-causmentioning
confidence: 99%